2022
DOI: 10.1002/jcu.23387
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐based radiomics in the diagnosis of carpal tunnel syndrome: The influence of regions of interest delineation method on mode

Abstract: Background In the recent years, artificial intelligence (AI) algorithms have been used to accurately diagnose musculoskeletal diseases. However, it is not known whether the particular regions of interest (ROI) delineation method would affect the performance of the AI algorithm. Purpose The purpose of this study was to investigate the influence of ROI delineation methods on model performance and observer consistency. Methods In this retrospective analysis, ultrasound (US) measures of median nerves affected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 35 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…1 The inclusion of the epineurium in the ROI as reported by Lv et al is supported by studies of the pathophysiology of CTS. [1][2][3][4][5][6][7] The pathology of CTS is characterized by entrapment of the MN at the transverse carpal ligament, resulting markedly increased pressure in the carpal tunnel as well as decreased neural gliding (tethering) with motion causing traction and shear forces on the MN. [2][3][4][5][6][7] As the pressure in the carpal tunnel increases, there is also interference with fluid flow in the small blood and lymphatic vessels that pass through the epineurium to supply the MN (Figure 2A).…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…1 The inclusion of the epineurium in the ROI as reported by Lv et al is supported by studies of the pathophysiology of CTS. [1][2][3][4][5][6][7] The pathology of CTS is characterized by entrapment of the MN at the transverse carpal ligament, resulting markedly increased pressure in the carpal tunnel as well as decreased neural gliding (tethering) with motion causing traction and shear forces on the MN. [2][3][4][5][6][7] As the pressure in the carpal tunnel increases, there is also interference with fluid flow in the small blood and lymphatic vessels that pass through the epineurium to supply the MN (Figure 2A).…”
mentioning
confidence: 62%
“…Lv et al have demonstrated that the epineurium should be included in the ROI for more consistent CTS measures 1 . Once reason that including the epineurium in the ROI provides more consistent results is likely due to the improved conspicuity of the epineurium‐extraneural connective tissue interface compared to more vague interfaces of the epineurium‐perineurium‐interfasicular interfaces (Figure 1).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations